Laser melting deposition of Inconel625/Ti6Al4V bimetallic structure with Cu/V interlayers - Wenbo Wang; Nuo Xu; Xiangyu Liu; Zhicheng Jing; Guojian Xu; Fei Xing (Materials Research Express, 2023)
A bimetallic structure (BS) made of Inconel625 (IN625) nickel-base superalloy with excellent high temperature properties and Ti6Al4V (TC4) titanium alloy with a light weight and a high strength has broad application prospects in aerospace engineering. However, the integrated manufacturing of the IN625/TC4 BS is a difficult research topic in the industry. In this work, the laser melting deposition (LMD) technology was used to prepare an IN625/TC4 BS without cracks and other metallurgical defects by adding Cu/V interlayers. The results show that the IN625/TC4 BS structure from the IN625 side to the TC4 one can be divided into four regions: IN625 region (region A) → Interlayers/IN625 transition region (region B) → TC4/Interlayers transition region (region C) → TC4 region (region D). The phase compositions of these regions are: γ -Ni + laves → (Ni, Cu)ss + (V, Cr)ss + TiNi → α -Ti + β -Ti + Ti _2 Ni → α -Ti + β -Ti. The Vickers hardness distribution is uneven in all regions, and the highest value (about 590.0 HV) is achieved in region B. The tensile strength of the IN625/TC4 BS with Cu/V interlayers reaches nearby 514.5±9.5 MPa at room temperature, and fractures are initiated in region B.